2013
DOI: 10.4028/www.scientific.net/amr.666.1
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Waste Plastics: Effect of Heating Rate on Product Yields and Oil Properties

Abstract: Selecting typical waste plastics, polyethylene (PE), polypropylene (PP) and polyvinyl chloride (PVC), and their mixture PE/PP/PVC as experimental samples, pyrolysis experiments were conducted on tubular furnace reactor at heating rates of 3.7 ℃•min -1 , 9.0 ℃•min -1 , 20.6 ℃•min -1 and 33.3 ℃•min -1 respectively to investigate effect of heating rate on yields of pyrolysis product (cracking oil, cracking gas and residue) and oil properties. The results showed that cracking oil yield was increased, but both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
2
1
0
2
Order By: Relevance
“…The trend of oil and gas production has increased and the solid product has decreased from the pyrolysis process is in agreement with the research conducted by Pei et al (2013) [13]. They reported that pyrolysis can be seen as a process for removing volatile materials from plastic waste.…”
Section: Yield Of Pyrolysis Productssupporting
confidence: 90%
See 1 more Smart Citation
“…The trend of oil and gas production has increased and the solid product has decreased from the pyrolysis process is in agreement with the research conducted by Pei et al (2013) [13]. They reported that pyrolysis can be seen as a process for removing volatile materials from plastic waste.…”
Section: Yield Of Pyrolysis Productssupporting
confidence: 90%
“…The highest heating value was produced by the pyrolysis process with 90 min residence time, which was 20.047 BTU/lb. This condition is in accordance with Pei (2013), where the heating value of oil formed from PE plastic will decrease with a decrease in the residence time, which was due to a decrease in the smaller number of hydrocarbon fractions that had high heating value in pyrolysis oil; therefore, the total calorific value of oil was smaller.…”
Section: Characteristics Of Pyrolysis Oilsupporting
confidence: 81%
“…The quite similar range also applies for HDPE, at 378-539 °C (Anuar Sharuddin et al, 2016). Besides temperature, the heating rate also brings a significant effect, either for conversion rate or product composition and calorific value (Tao et al, 2013).…”
Section: Introductionmentioning
confidence: 64%
“…Hasil penelitian menunjukkan bahwa rendemen minyak akan meningkat seiring dengan kenaikan laju pemanasan, akan tetapi rendemen gas dan residu padatan akan menurun. Variasi dari distribusi senyawa di dalam minyak yang dihasilkan dari bermacam-macam plastik juga berbeda antara satu sama lain [18].…”
Section: Gambar 1 Target Bauran Energi Nasionalunclassified
“…Lebih spesifik lagi, jika suhu proses sangat tinggi, maka bahan organik dengan titik didih dan berat molekul yang besar, yang selama ini tertinggal sebagai bagian dari residu padatan, akan terlepas dalam bentuk gas yang menguap. Pada akhirnya, gas-gas yang menguap tersebut akan terkondensasi menjadi minyak [18].…”
Section: Grafik 5 Pengaruh Laju Kenaikan Suhu Terhadap Rendemen Produnclassified